Análisis sociolingüístico de los discursos ambientales sobre la Amazonía (2004)
ABSTRAC: The debates around the planning of the Amazons become more and more frequent and complex. Some of them plead for the intact conservation of this natural reservation humanity’s biological and cultural patrimony, while others argue that this will only be preserved by means of their sustainable commercial use. The present article tries to show how such divergences and contradictions are explained partly by the social, environmental and economic contexts where these discussions take place, appealing for it to the sociolinguistic analysis of the speech proposed by Bourdieu and Jociles, where the social conditions of production of the speech, explain partially its content, structures, and true premeditation (Bourdieu, 1985). The study points out how the speech can be constituted in a tool of great symbolic power through which is possible to give genuineness to a series of supremely controversial events and finally it concludes that if the complete objectivity of the discursive practices is technically impossible, it becomes strictly necessary, mainly in debates so complex as those that concern the Amazons, to investigate the social conditions in which these take place.